Code Switching And Code Mixing In Film Habibie & Ainun 3 - Narendrari A. Edhi; Yunanfathur Rahman (Universitas Negeri Surabaya, 2021)
Code switching is used when a speaker switches language to another language. It usually occurs in a multilingual society. Code switching can be divided into two, namely internal code switching and external code switching. Not only code switching, there is also code mixing. Code mixing is used when a speaker mixes two languages at once in one discussion. Therefore, the researcher chose to conduct code switching and code mixing research in the film entitled Habibie & Ainun 3. The purpose of this study was to find SPEAKING-aspects from Hymes as well as code switching and code mixing in the film's dialogues. The method used is descriptive method. The results obtained 10 data consisting of 6 code-switching data, 1 code-mixing data, and 3 code switching and code mixing data. Keywords: code switching, code mixing, film, SPEAKING